Crossmodal Correspondences in the Sounds of Chinese Instruments. (January 2020) - Qi, Yuxuan; Huang, Fuxing; Li, Zeyan; Wan, Xiaoang
People tend to associate stimuli from different sensory modalities, a phenomenon known as crossmodal correspondences. We conducted two experiments to investigate how Chinese participants associated musical notes produced by four types of Chinese instruments (bowed strings, plucked strings, winds, and percussion instruments) with different colors, taste terms, and fabric textures. Specifically, the participants were asked to select a sound to match each color patch or taste term in Experiment 1 and to match the experience of touching each fabric in Experiment 2. The results demonstrated some associations between pitch and color, taste term, or the smoothness of fabrics. Moreover, certain types of Chinese instruments were preferentially chosen to match some of the colors, taste terms, and the texture of certain fabrics. These findings therefore provided insights about the perception of Chinese music and shed light on how to apply the multisensory features of sounds to enhance the composition, performance, and appreciation of music.